Insight into the Recent Genome Duplication of the Halophilic Yeast Hortaea werneckii: Combining an Improved Genome with Gene Expression and Chromatin Structure. Issue 7 (1st July 2017) - Sinha, Sunita; Flibotte, Stephane; Neira, Mauricio; Formby, Sean; Plemenitaš, Ana; Cimerman, Nina Gunde; Lenassi, Metka; Gostinčar, Cene; Stajich, Jason E; Nislow, Corey
Abstract: Extremophilic organisms demonstrate the flexibility and adaptability of basic biological processes by highlighting how cell physiology adapts to environmental extremes. Few eukaryotic extremophiles have been well studied and only a small number are amenable to laboratory cultivation and manipulation. A detailed characterization of the genome architecture of such organisms is important to illuminate how they adapt to environmental stresses. One excellent example of a fungal extremophile is the halophile Hortaea werneckii (Pezizomycotina, Dothideomycetes, Capnodiales), a yeast-like fungus able to thrive at near-saturating concentrations of sodium chloride and which is also tolerant to both UV irradiation and desiccation. Given its unique lifestyle and its remarkably recent whole genome duplication, H. werneckii provides opportunities for testing the role of genome duplications and adaptability to extreme environments. We previously assembled the genome of H. werneckii using short-read sequencing technology and found a remarkable degree of gene duplication. Technology limitations, however, precluded high-confidence annotation of the entire genome. We therefore revisited the H. wernickii genome using long-read, single-molecule sequencing and provide an improved genome assembly which, combined with transcriptome and nucleosome analysis, provides a useful resource for fungal halophile genomics. Remarkably, the ∼50 Mb H. wernickii genome contains 15, 974 genes of which 95% (7608) are duplicates formed by a recent whole genome duplication (WGD), with an average of 5% protein sequence divergence between them. We found that the WGD is extraordinarily recent, and compared to Saccharomyces cerevisiae, the majority of the genome's ohnologs have not diverged at the level of gene expression of chromatin structure.